Numerical Study of Liquid Film Characteristics at Varying Operating Conditions in Prefilmer Airblast Atomizer. Issue 1 (11th December 2015) - Volz, Melanie; Nittel, Lena; Habisreuther, Peter; Zarzalis, Nikolaos
Abstract: The atomization of liquid fuel in gas turbines is one of the key factors that affect the combustion performance. After the adaptation of the k‐ϵ ‐turbulence model for two‐phase flows and the definition of the film thickness, this work investigates and reports the influence of different parameters on the behavior of the liquid film on the prefilmer of airblast atomizers. A correlation that can be used to predict the mean film thickness has been developed and is proposed in the present study. This correlation can be used in order to optimize the design of airblast atomizers. Abstract : The behavior of shear‐driven liquid films on the prefilmer of airblast atomizers is often characterized with the help of Weber number, which cannot predict the complex interaction on the film correctly. In this work a correlation is presented as alternative for calculating the mean film thickness on the prefilmer under desired boundary conditions.